Frontispiece: NMR Hyperpolarization Techniques of Gases. Issue 4 (20th January 2017) - Barskiy, Danila A.; Coffey, Aaron M.; Nikolaou, Panayiotis; Mikhaylov, Dmitry M.; Goodson, Boyd M.; Branca, Rosa T.; Lu, George J.; Shapiro, Mikhail G.; Telkki, Ville‐Veikko; Zhivonitko, Vladimir V.; Koptyug, Igor V.; Salnikov, Oleg G.; et al.
Abstract : Hyperpolarization The fundamentals of preparation of hyperpolarized gases are detailed with a focus on selected applications of hyperpolarized gases to provide illustrative examples of their utility in biomedicine and materials sciences: remote detection, pulmonary imaging, gas‐phase imaging, time‐of‐flight imaging, brown‐fat imaging, and other imaging and spectroscopic applications. For more details, see the Minireview by E. Y. Chekmenev et al. onpage 725 ff.